Leadership through the perspectives of high-ranking leader for TVET organisational excellence in Malaysia - Ahmad, Hadijah (2018)
This phenomenological qualitative inquiry is designed to explore key characteristics of leaders, which includes seeking their perspectives regarding the phenomena of Technical Vocational Education and Training (TVET) organisational excellence beside the societal stigma from society. The aims of this study encompasses the leadership and TVET perspectives, roles, characteristics and challenges, alongside TVET organisational excellence, strategies and aspiration of high-ranking TVET leaders towards championing it in Malaysia. As TVET transformation is pionereed by high ranking leaders, the need for studies to be conducted on the topic are justified especially due to the minimal amount of knowledge available. This study has involved seven high-ranking leaders in various organisations in Malaysia who are vastly experienced in TVET. Data collection has been carried out using semi structured in-depth interview with a developed interview protocol. Participant‘s live experience has subsequently been subjected to conventional data analysis techniques like manual coding and Nvivo 8. Interpretation of the findings has then been made via thematic analysis, revealing 7 themes and 18 emerged subthemes in the study. The research question 1 explicates leaders define leadership as a language game where there is no agreeableness on the definition while leaders define TVET education as both mental and physical activity. Research question 2 explicates 2 forms of leadership characteristic for TVET high-ranking leaders consists of TVET leadership capabilities based on theoretical concept and TVET leadership competencies in 4 areas. TVET leaders role in international, organisation and society and also TVET leadership effectiveness by roles answer the research question 3. Research question 4 answered by 2 challenges faced by TVET high ranking leaders includes TVET disorder and human element. TVET organizational excellence as perceived by high-ranking leaders consist of awareness, KSA graduates and potent TVET system to answer research question 5. There are 6 strategies to positioning TVET organisational excellence such as transformation, unity, stakeholder buy-in, collaboration, TVET talent and media roles to answer research question 6. The future hopes for TVET organisational excellence delineates more partnership between industry and public-private institutions as an answer to research question 7. The extracts of their ‗brain collections‘ serve as exclusive recipes for TVET organisational excellence, yielding substantive information to help practitioners in raising TVET images and allow it to soar beyond.